1975
DOI: 10.1037/0022-0663.67.5.643
|View full text |Cite
|
Sign up to set email alerts
|

Field dependence and the school achievement gap between Anglo-American and Mexican-American children.

Abstract: Research supports the hypothesis that field dependence explains the poorer school achievement of Mexican-American children compared to Anglo-American children. To test that hypothesis, multiple regression and path analyses were used to interpret the relationships between culture, field dependence, and school achievement among 134 2nd-, 4th-, and 6th-grade Anglo-American and Mexican-American children. Results indicate that Mexican-Americans were significantly below Anglo-Americans in reading and math achievemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
30
3

Year Published

1980
1980
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(36 citation statements)
references
References 13 publications
3
30
3
Order By: Relevance
“…The results of a study by Hansen (1994) indicate a significant difference between groups of students based on ethnic origin (Asian, Hispanic, White). The results of the study confirm the findings of a number of researchers who found that ethnic minority students were more fielddependent than white students (Castenada et al, 1972;Kagan and Zahn, 1975;Ramirez and PriceWilliams, 1974). The implication is that instructional approaches must appeal to field-dependent individuals as well as field-independent individuals to ensure that instruction is not biased to favor individuals on the basis of gender or member of ethnic or racial groups.…”
Section: Field Articulationsupporting
confidence: 81%
“…The results of a study by Hansen (1994) indicate a significant difference between groups of students based on ethnic origin (Asian, Hispanic, White). The results of the study confirm the findings of a number of researchers who found that ethnic minority students were more fielddependent than white students (Castenada et al, 1972;Kagan and Zahn, 1975;Ramirez and PriceWilliams, 1974). The implication is that instructional approaches must appeal to field-dependent individuals as well as field-independent individuals to ensure that instruction is not biased to favor individuals on the basis of gender or member of ethnic or racial groups.…”
Section: Field Articulationsupporting
confidence: 81%
“…These results are supported by another study by Saracho (1983e). Such evidence challenges that of earlier studies by other researchers (e.g., Buriel, 1975;Kagan & Zahan, 1975;Ramirez & Price-Williams, 1974;Sanders, Schols & Kagan, 1976) and suggests that it is not possible to generalize about the Mexican American children's social orientation and their cognitive style even at an early age. FDI is a relative rather than an absolute term, Since extensive data must be collected and analyzed before accepting any generalizations, the assumption that Mexican Americans are all FD cannot be accepted.…”
Section: Cognitive Stylescontrasting
confidence: 69%
“…Studies on the cognitive style of Mexican Americans suggest that they are more FD than Anglo Americans (Buriel, 1975;Canavan, cited in Kagan & Buriel, 1977;Kagan & Zahan, 1975;Ramirez, 1973;Ramirez & Price-Williams, 1974;Sanders, Scholz & 23 Kagan, 1976). These outcomes have been attributed to the traditional child rearing practices of the Mexican American families (Dyk & Witkin, 1965;Saracho & Hancock, 1983).…”
Section: Cognitive Stylesmentioning
confidence: 99%
“…Similar to this orientation is Lambert & Gardner's (1968) discussion of integrative and instrumental motivation, the distinction being viewing an activity as an end in itself (sidestream) or as the means to an end (mainstream). Others mention many of these same distinctions under the Downloaded by [University of Newcastle (Australia)] at 08:15 05 October 2014 rubric of field dependence vs. field independence (Schumann, 1978;Sanders, Scholz & Kagan, 1976;Ramírez, Castañeda & Herold, 1974;Kagan & Zahn, 1975). The field independent person (mainstream) is said to be able to break the whole down into parts whereas the field dependent person (sidestream) is believed to have a more wholistic view:…”
Section: Bilingual Education and The Role Of The Schoolsmentioning
confidence: 99%
“…This 'achievement gap' (Kagan & Zahn, 1975) has been attributed to a variety of factors. There are those who blame the Mexicans and see their failure in the schools as the result of negative attitudes and low aspirations.…”
Section: Introductionmentioning
confidence: 99%